Depositional history and characterisation of Eocene carbonate reservoirs and their outcrop analogues, Tarabulus and Cyrenaica Basins, Northern Libya - Imbarek, Omar Mohamad Abdulssalam (Curtin University, 2018)
The Eocene carbonates are the most important hydrocarbon reservoirs in Libya as they constitute a significant amount of hydrocarbons in Tarabulus Basin, northwestern offshore Libya. This research is designed to integrate and interpret geophysical and sedimentological data including seismic reflections, well-logs, cores-field-based data, and petrographic data for detailed petroleum geology investigation. This will include the salt tectonic phenomena in the basin, lithofacies analyses, depositional environments, diagenetic history, and outcrop-analogue reservoir modelling.